AN INVESTIGATION OF THE PREDICTIVE RELATIONSHIPS BETWEEN IDENTIFIED FACTORS AND GRADUATE STUDENTS' DECISION TO STUDY HUMAN SCIENCES PROGRAMS AT ASSUMPTION UNIVERSITY - TRAIBUTRA, RANGSAN; AYATHUPADY MOHANAN, SANTHOSH (Scholar: Human Sciences, 2022)
This quantitative study was aimed to identify predicable factors, different choices between the male and the female graduate students and different choice between Thai and non-Thai graduate students to enroll in the Human Sciences programs in Assumption University. 400 quota samples were distributed with e-questionnaire for data collection. Descriptive statistics, Omnibus Tests of Model Coefficients, Hosmer and Lemeshow Test and Logistic Regression Analysis were applied to Statistical Analysis. It was found Program Characteristics, Institution Characteristics, and Interest in the Subject were the highly significant predictors on decision to enroll in the Human Sciences programs. Institution Characteristics, and Program Characteristics significantly differentiated the male students’decision whereas the Program Characteristics, Institution Characteristic and Interest in the Subject significantly differentiated the female candidates’ decision to enroll in the Human Sciences programs. The Interest in the Subject was the significant factor over Thai students’ decision whereas Institution Characteristics, the Program Characteristics and the Influence of People and Media respectively were highly significant factors over the non-Thai students’ decision to enroll in the mentioned program. All the three hypotheses were accepted.